2017
DOI: 10.1111/1745-9125.12132
|View full text |Cite
|
Sign up to set email alerts
|

Judicial Rotation as Centripetal Force: Sentencing in the Court Communities of South Carolina*

Abstract: Courts as communities theory emphasizes the sentencing differences that can arise between localities within a single state. The results of published studies have highlighted how local differences emerge based on informal sociological and political processes defined by the communities perspective. The findings from recent quantitative studies from South Carolina have revealed notably less county variation in sentencing than has been observed elsewhere. I use qualitative interviews with 13 South Carolina trial j… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 78 publications
2
20
0
Order By: Relevance
“…Comparing the disparities resulting from judges who were observed to rotate across courts against those who stayed in the same court, we found that judges working in multiple courts sentence a more heterogeneous and complex caseload, but do so more consistently than judges who stay in the same court. These results corroborate Hester (2017), who, based on qualitative interviews with thirteen judges from South Carolina, indicates that judicial rotation seems to facilitate the spread of norms and homogenize judicial sentencing practices. Indeed, exposure to other judges and court actors may support consistent sentencing practices.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Comparing the disparities resulting from judges who were observed to rotate across courts against those who stayed in the same court, we found that judges working in multiple courts sentence a more heterogeneous and complex caseload, but do so more consistently than judges who stay in the same court. These results corroborate Hester (2017), who, based on qualitative interviews with thirteen judges from South Carolina, indicates that judicial rotation seems to facilitate the spread of norms and homogenize judicial sentencing practices. Indeed, exposure to other judges and court actors may support consistent sentencing practices.…”
Section: Discussionsupporting
confidence: 87%
“…Typically, variations in sentence length or type, stemming from any of the levels listed above, which cannot be explained by legitimate case characteristics (e.g., offence severity), are used as measures of inconsistency in sentencing. These studies are premised (implicitly or explicitly) on the 'court communities' perspective (Hester, 2017). This theory views courts as communities made up of actors such as prosecutors, judges, defence lawyers, and court staff (Eisenstein, Flemming and Nardulli 1988;Flemming, Nardulli and Eisenstein 1992;Ulmer 1997).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inter‐judge disparity is a rich area of research, which has continued to grow to capture newly realized influences upon a judge's sentencing behavior (Anderson & Spohn 2010; Bushway et al 2012; Hester 2017; Krasnostein & Freiberg 2013; Marder & Pina‐Sánchez 2018; Myers 1988; Roberts & Ashworth 2016; Tonry 1996; Ulmer & Johnson 2017; Yang 2014). Early studies focused on seemingly biased treatment based on offenders’ traits, such as their race, gender, and socioeconomic status (the basis of focal concerns theory within sentencing that predominates in the criminology literature) (Steffensmeier 1980; Steffensmeier et al 1998).…”
Section: Literature Review: Inter‐judge Disparitymentioning
confidence: 99%
“…Despite this, sentencing studies have underscored the prominence of inter‐judge disparity in sentence outcomes (Anderson & Spohn 2010; Bushway et al 2012; Hester 2017; Krasnostein & Freiberg 2013; Marder & Pina‐Sánchez 2018; Roberts & Ashworth 2016; Yang 2014). Inter‐judge disparity is defined as the relative differences in average sentence lengths for comparable caseloads assigned to different judges (Anderson et al 1999).…”
Section: Introductionmentioning
confidence: 99%